A 2020 vision for food, agriculture, and the environment in southern Africa - Pinstrup-Andersen, Per; Pandya-Lorch, Rajul; Babu, Suresh Chandra (International Food Policy Research Institute, 1997)
Following considerable political, social, institutional, and economic transformations, particularly in the last 5 to 10 years, Southern Africa today, more than ever before, has the potential assure a better and more secure world for its people now and in the future. However, reversing the trends of recent decades-widespread poverty, hunger, and mal nutrition; rapid population growth; massive displacements of populations; conflicts over and mistreatment of natural resources; and insufficient investment in development-will depend on adopting appropriate policies and reallocating resources. Pursuit of poor policies could condemn the region to ignore human misery and degradation of natural resources, which in turn would impose misery on future generations and cause continued misallocation of resources, social and political instabilities, and falling living standards for all.